2019
DOI: 10.1016/j.fochx.2018.100003
|View full text |Cite
|
Sign up to set email alerts
|

Formation of disinfection byproducts in wash water and lettuce by washing with sodium hypochlorite and peracetic acid sanitizers

Abstract: Highlights Formation of disinfection byproducts (DBPs) by NaOCl and PAA washing was compared. Wash water and lettuce were analyzed for 45 conventional and emerging DBPs. PAA formed much less chlorinated DBPs than NaOCl in wash water and lettuce. PAA formed slightly less aldehyde DBPs than NaOCl in wash water and lettuce. The DBPs formation patterns varied in wash water compared to washed lettuce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 32 publications
0
39
0
1
Order By: Relevance
“…PAA‐based sanitizers offer additional advantages, including easy application in commercial settings, effective in inactivating a broad spectrum of foodborne pathogens and stable antimicrobial efficacy in presence of varying organic loads (Flores and others ). In a very recent study Lee and Huang () reported as compared with sodium hypochlorite solution, washing lettuce with PAA generated fewer disinfection byproducts in fresh‐cut lettuces. The wash water generated after washing lettuce with PAA also contained fewer disinfection byproducts compared to that of sodium hypochlorite.…”
Section: Resultsmentioning
confidence: 99%
“…PAA‐based sanitizers offer additional advantages, including easy application in commercial settings, effective in inactivating a broad spectrum of foodborne pathogens and stable antimicrobial efficacy in presence of varying organic loads (Flores and others ). In a very recent study Lee and Huang () reported as compared with sodium hypochlorite solution, washing lettuce with PAA generated fewer disinfection byproducts in fresh‐cut lettuces. The wash water generated after washing lettuce with PAA also contained fewer disinfection byproducts compared to that of sodium hypochlorite.…”
Section: Resultsmentioning
confidence: 99%
“…For example, chlorine washes lose much of their effectiveness in the presence of organic material (Herdt & Feng, ; Mahajan et al, ). Both chlorine and, to a lesser extent, PAA produce a number of chemical byproducts after treatment (Lee & Huang, ), and importantly, those produced after chlorine washes are known carcinogens (Herdt & Feng, ; Mahajan et al, ). Directly related to human health and nutrition, chlorine and PAA are strong oxidative agents capable of deleteriously impacting the nutritional value of certain foods, for example, by destroying health‐associated compounds such as polyphenols (including flavonoids), vitamin C, and the overall antioxidant capacity of certain foods (Choi & Sapers, ; Van de Velde, Grace, Pirovani, & Lila, ).…”
Section: Introductionmentioning
confidence: 99%
“…Organic radicals are commonly generated from the activation of peroxide bond in the organic peroxy acid, such as peracetic acid (PAA, CH 3 C(O)OOH) [16,17]. PAA is known as a broad-spectrum antimicrobial agent and has been widely used as an alternative to conventional chlorine disinfectants in wastewater disinfection, owing to the advantages of PAA, such as strong oxidation power (redox potential ranging from 1.06 to 1.96 V) [18] and a low potential of harmful disinfection byproduct generation [19][20][21]. PAA is produced by the reaction of acetic acid and H 2 O 2 in the presence of a strong acid catalyst, such as sulfuric acid [22][23][24], and thus the commercial PAA solution is an equilibrium solution with acetic acid and H 2 O 2 according to Equation (1).…”
Section: Introductionmentioning
confidence: 99%